2020
DOI: 10.3390/v12070739
|View full text |Cite
|
Sign up to set email alerts
|

Infection of a Lepidopteran Cell Line with Deformed Wing Virus

Abstract: Many attempts to develop a reliable cell cultured-based system to study honey bee virus infections have encountered substantial difficulties. We investigated the ability of a cell line from a heterologous insect to sustain infection by a honey bee virus. For this purpose, we infected the Lepidopteran hemocytic cell line (P1) with Deformed wing virus (DWV). The genomic copies of DWV increased upon infection, as monitored by quantitative RT-PCR. Moreover, a tagged-primer-based RT-PCR analysis showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The study also found DWV in nearby plant-feeding beetles, bugs, and butterflies (Levitt et al, 2013); these were likely infected horizontally by feeding on pollen that had been contaminated by infected bees (Bailes et al, 2018;Mazzei et al, 2014). A recent study showed that DWV can replicate in a heterologous Lepidopteran cell line (P1) and harvested virus can also infect honey bees (Erez and Chejanovsky, 2020).…”
mentioning
confidence: 68%
“…The study also found DWV in nearby plant-feeding beetles, bugs, and butterflies (Levitt et al, 2013); these were likely infected horizontally by feeding on pollen that had been contaminated by infected bees (Bailes et al, 2018;Mazzei et al, 2014). A recent study showed that DWV can replicate in a heterologous Lepidopteran cell line (P1) and harvested virus can also infect honey bees (Erez and Chejanovsky, 2020).…”
mentioning
confidence: 68%
“…Experiments in cultured honey bee cells also provide an opportunity to study the mechanistic details of DWV infections and virus–host dynamics in a system that complements experiments carried out in larvae, pupae, and adult honey bees. Recent efforts have focused on exploring the ability of alternative host cell lines to support honey bee virus infections; for example, the Lepidopteran hemocyte-derived cell line (P1) has been shown to support DWV infection [ 151 ]. While exploring the ability of alternative cell lines to support honey bee virus infections is an attractive approach, the immune response elicited by these alternative host cells may or may not completely recapitulate the immune response elicited by honey bees.…”
Section: Resultsmentioning
confidence: 99%
“…While an important step towards the development of immortalized honey bee cell lines, AmE-711 has a long doubling time, is difficult to maintain in other labs, and it is persistently infected with DWV [ 10 ]. Therefore, the use of non-honey-bee cells lines, including the Lepidopteran hemocytic cell line (P1), to study honey-bee-infecting viruses, including DWV, have been explored and will likely serve as an important tool for investigating bee viruses at a cellular level [ 8 , 151 ]. While immortalized cell cultures provide a convenient and consistent tool, they often do not fully recapitulate in situ biology.…”
Section: Introductionmentioning
confidence: 99%
“…Common lepidopteran insect cell lines may have difficulties serving as alternative hosts for selecting and proliferating bee-infecting virus isolates or infectious cDNA clones. Spodoptera frugiperda cell lines, one of the widely available insect cell lines, may not host the viruses ( 24 , 25 ). We have transfected the full-length SBV RNA from our previous work ( 14 ) into Sf9 cells and identified the produced virions using RT-qPCR with RNase treatment in preliminary trials, but we found the produced virions were low in quantities and not able to be passaged in Sf9 cells, similar to what has been published by ( 25 ).…”
Section: Obtaining Cdna Templatesmentioning
confidence: 99%